Residual Stress, Thermomechanics & Infrared Imaging, Hybrid Techniques and Inverse Problems, Volume 8 Proceedings of the 2017 Annual Conference on Experimental and Applied Mechanics (Conference Proceedings of the Society for Experimental Mechanics Series,, 2018)
Residual Stress, Thermomechanics & Infrared Imaging, Hybrid Techniques and Inverse Problems, Volume 8 of the Proceedings of the 2017 SEM Annual Conference & Exposition on Experimental and Applied Mechanics, the eighth volume of nine from the Conference, brings together contributions to this important area of research and engineering. The collection presents early findings and case studies on a wide range of areas, including: Residual Stress Measurements Stress Analysis from Thermal Measurements Damage & Defect Analysis Using Infrared Techniques Inverse Methods in Plasticity Inverse Problem Methodologies in Experimental Mechanics.